A primer on property tax administration and policy - McCluskey, William J.; Cornia, Gary C.; Walters, Lawrence C. (Hoboken, N.J. : Wiley, 2013)
This encyclopedia provides an in-depth analysis of issues related to property taxation, including law, public finance, decentralization, valuation, and property tax form. This encyclopedia examines the criteria applied to evaluate the strengths and weaknesses of property tax. This text also discusses the main valuation methods and the economic principles underpinning them, and reviews the legal and administrative aspects of property tax. Providing topical and highly relevant material, this text also looks at various efforts to reform the property tax in countries that have systems in place dee.
4 Administration of Local Taxes: An International Review of Practices and Issues for Enhancing Fiscal autonomy1Introduction; Central administration; Some national experiences; Results from central administration; Independent local administration; Experience with local administration; The special case of property taxes; Results from independent local administration; Share, joint and cooperative administration; Conclusion; Note; References; 5 Establishing a Tax Rate; Introduction; What level of government should set the property tax rate?; Setting the property tax rate; Determining the tax base.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Property tax; Property tax -- Law and legislation; Taxation; BUSINESS & ECONOMICS -- International -- Taxation; Property tax; Property tax -- Law and legislation; Electronic books; Electronic books